Transforming Education Design & Governance in Global Contexts (Springer Singapore, 2018)
This book is an edited collection grouped into three key thematic areas. Its authors are researchers and theoretical scholars in the fields of education curriculum, education technology, education philosophy, and design for education. They present primary research and theoretical considerations, descriptive accounts and philosophical reflections to provide readers with a broad sweep of the 'state of play' in thinking about the place and space of learning. Transforming Education distils, from a panoply of critical arenas, an understanding of the forces currently at play in redefining curriculum agendas for education - from primary to post-secondary. It analyses the major ways in which the built environment of education is transforming, in response to various globalised policy drivers and new education delivery technologies. Its authors critique the ways education performs a governance function over the users and occupants of space, be it physical or virtual. F or readers who may be seriously engaging with the concept of spatiality in relation to education for the first time, this book provides the opportunity to develop a clear understanding of a wide scope of theory, practice and critique in relation to learning environments.